Analisis Kepuasan Pengguna Lulusan Kerja Praktek Industri Mahasiswa Politeknik Maritim Negeri Indonesia - Susanti Susanti; Masriah Masriah (Jurnal Maritim Polimarin, 2021)
Politeknik Maritim Negeri Indonesia (POLIMARIN) Semarang is a vocational higher education institution in the maritime field that annually graduated alumni spread throughout the business world and the industrial world in accordance with their fields.This study aims to look at the level of satisfaction of the business and industry institutions towards graduates of industry practices related to soft skills and hard skills and other elements.The research method is a descriptive method. Method of collecting survey data through questionnaires post fact. The respondents were 30 person as user companies graduated from industrial practice. The questionnaire answers use a Likert scale with calculations to find GAP, where GAP is the difference between the value of reality and the value of expectations of the business and industrial institutions to the quality of graduates. The role of stakeholders can not be ruled out, because they are the users of graduates from Polimarin, especially the first study program KPN. Stakeholder needs and assessment can be used as evaluation tools by Polimarin in improving the quality of graduates, ensuring that graduates have the ability and expertise in accordance with the needs of graduate’s users and used as feedback in order to improve the overall quality of graduates.